1943
DOI: 10.1021/ja01250a034
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Surface Area in Silica Aerogel

Abstract: Tyndall beam which we use, but we have been able to determine its rate of coagulation with Mr.Green's condensation apparatus."Likewise, the electrification produced upon the disruption of materials and surfaces is well known.7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1947
1947
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Other reports of reversible sorption in the silica gel-water sys¬ tem are scarce indeed. Within recent years, however, Kistler, Fischer, and Freeman (19) have reported that their results indicate reversibi¬ lity of the desorption cycle. Although they obtained isothermal pres-✓ sure concentration diagrams showing considerable hysteresis, they be¬ lieve that if certain correction factors in connection with their ex¬ perimental arrangements were applied, the equilibrium values for p-c obtained during desorption would be within experimental error of those observed under conditions of increasing water concentration* More recently, Taylor (30) determined Isoteres for the water vaporsilica gel system.…”
Section: Table I Imentioning
confidence: 99%
“…Other reports of reversible sorption in the silica gel-water sys¬ tem are scarce indeed. Within recent years, however, Kistler, Fischer, and Freeman (19) have reported that their results indicate reversibi¬ lity of the desorption cycle. Although they obtained isothermal pres-✓ sure concentration diagrams showing considerable hysteresis, they be¬ lieve that if certain correction factors in connection with their ex¬ perimental arrangements were applied, the equilibrium values for p-c obtained during desorption would be within experimental error of those observed under conditions of increasing water concentration* More recently, Taylor (30) determined Isoteres for the water vaporsilica gel system.…”
Section: Table I Imentioning
confidence: 99%
“…He synthesized a silica-based aerogel via a wet chemical sol-gel process and subsequent supercritical solvent extraction [1,2]. The aerogel showed unique material properties such as high optical transparency or opacity, heat insulation capability, and high absorption capacity [3,4]. These properties led to the use of silica aerogels in ion exchange materials, adsorbents, semipermeable membranes, pharmaceuticals, cosmetics, optical and acoustical devices, coating materials, and heat insulation applications for buildings [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This method is valid in the cases of nonporous and macroporous adsorbents only. In the case of mesopo rous adsorbents, the methods based on works [34,35] and the method developed in full by Kiselev [36] are most widely used. According to [36], the adsorption film surface in mesopores can be given by the follow ing equation:…”
Section: Analysis Of the Main Methods Of Determining The Specific Surmentioning
confidence: 99%